‘This is where we buried our sons’ : people of advanced old age coping with the impact of the AIDS epidemic in a resource-poor setting in rural Uganda - Seeley, Janet; Wolff, Brent; Kabunga, Elizabeth; Tumwekwase, Grace; Grosskurth, Heiner (Ageing & Society, 2009)
Much research on the impact of HIV and AIDS on older people fails to differentiate between age groups, and treats those aged from 50 years to the highest ages as homogeneous. The ‘oldest old’ or those aged over 75 years may be particularly vulnerable through declining health and independence as a result of the AIDS epidemic, which has forced some to take on roles that younger relatives would have performed had they lived. In this paper we describe the past and current experience of eight people in advanced old age living in rural Uganda who were informants for an ethnographic study of the impact of HIV and AIDS on households during 1991–92 and again in 2006–07. The aim of the study was to understand how they had coped with the impacts of the epidemic. From the eight case studies, it is concluded that family size, socio-economic status and some measure of good fortune in sustained good health enabled these people to live to an advanced age. While we recommend that targeted social protection is important in helping the poorest among the oldest, we suggest that sustaining respect for age and experience, and ensuring that older people do not feel discarded by family and society are as important as meeting their practical needs.
Keywords: older people, oldest old, impact of HIV and AIDS, Uganda.